Appropriate antimicrobial therapy in the era of multidrug-resistant human pathogens. (April 2015) - Pogue, J.M.; Kaye, K.S.; Cohen, D.A.; Marchaim, D.
Abstract: The past decade has brought a significant rise in antimicrobial resistance, and the ESKAPE pathogens have become a significant threat to public health. Three epidemiological features that negatively impact patients, which are consistently seen with the ESKAPE pathogens, are the following: 1) there has been a rise in incidence of these organisms as causative human pathogens, 2) there has been a significant increase in antimicrobial resistance in these bacterial species, and 3) the infections caused by these resistant strains are associated with worse outcomes when compared with infections caused by their susceptible counterparts. Significant delays in time to appropriate antimicrobial therapy of up to 5 days have been reported in infections due to these organisms and this is the strongest predictor of mortality with ESKAPE pathogens, particular in critically ill patients, where every hour delay has an incremental survival disadvantage for patients. Strategies to decrease these delays are urgently needed. Although routine broad-spectrum empiric coverage for these organisms would ideally limit this delay, agents with activity against these organisms are sometimes less effective, have significant toxicity risk, and their use can result in the development of resistance. Therefore, strategies to optimize therapy, although limiting unnecessary use of broad-spectrum antimicrobials, are urgently needed. This review will discuss potential strategies to optimize empiric therapy in the age of multi-drug resistance, the limitations of these strategies, and will discuss future directions and opportunities.